MENAKAR KUALITAS INFORMASI LAPORAN KEUANGAN PEMERINTAH DAERAH MELALUI FAKTOR-FAKTOR PENENTUNYA (Studi Empiris pada SKPD di Kota Semarang) - Intan Ayuningtyas; Ardiani Ika Sulistyawati; , Arief Himmawan Dwi Nugroho (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2022)
This research aims to test and analyze the influence of internal control systems, information technology utilization, human resources quality, implementation good governance, and human resource capacity toward the quality of the financial information of local government. The sample in this research were employees of the finance department at SKPD in Semarang. Sampling techniques carried out by purposive sampling method that produces 124 samples to be processed. The analysis method used in this research is a quality test of data, classic assumptions test, hypothesis test and multiple linear regression analysis with SPSS program. The results show that the partial implementation of information technology utilization and human resources quality have a positive effect on the quality of local government financial reporting information, while the use of internal control systems, implementation good governance, and human resource capacity does not have an effect on the quality of local government financial reporting information. While simultaneously the analyze the influence of internal control systems, information technology utilization, human resources quality, implementation good governance, and human resource capacity together affect the quality of the financial information of local government.